Harvester ants (Messor barbarus) as disturbance agents in Mediterranean grasslands - Azcárate, F. M.; Peco, B. (Journal of Vegetation Science, 2009)
Questions: 1. Do disturbances by harvester ants (Messor barbarus L.) affect soil properties? 2. Do they alter seed distribution? 3. Do they show a different species composition? 4 Are these changes related to seed size (length and weight)? Location: Mediterranean grasslands in central Spain, near Madrid. Methods: We recorded autumn seed banks and spring vegetation in middens, trunk trails and controls. Soil properties were also measured in middens and controls. The effect of seed weight and length was analysed after transforming data into phylogenetically independent contrasts. Results: Soil under middens is more silty and higher in potassium, organic matter and pH. Seed density and seed bank species richness increased greatly in middens, while vegetation species richness was signiﬁcantly lower in comparison to control samples. Abundance changes in this disturbance type were positively correlated with seed weight, both in seed bank and vegetation. In contrast, we only detected a slight increase in bare ground on foraging trunk trails, with no clear effects on seed bank and vegetation composition. Conclusions: Midden development is a mechanism that generates heterogeneity which favours the survival of certain large-seeded species mainly predated by ants in Mediterranean grasslands. This effect may partially neutralize the dominance of small seeded species expected from the seed predation process.
Keywords: midden; seed bank; Seed size; soil property; Trunk trail

Drosophyllum lusitanicum, an endangered West Mediterranean endemic carnivorous plant: threats and its ability to control available resources - Correia, E.; Freitas, H. (BOTANICAL JOURNAL OF THE LINNEAN SOCIETY, 2002)
Drosophyllum lusitanicum (L.) Link (Droseraceae), Erva pinheira orvalhada, an endangered carnivorous plant, is a local endemic of clearings in pine, cork oak and oak forests or their successional shrublands in the western Iberian Peninsula and Morocco. The conservation status, distribution and population dynamics of this species are only partially known, both for Spanish and Portuguese occurrences. Portuguese distribution data from herbarium and bibliographic sources were collected for this study. Field work on 50 populations was undertaken in order to improve knowledge on their conservation status and possible threats. Natural causes, infrastructure and housing construction are stressed as the most important threats. Germination tests were carried out and the distribution patterns, plant height and the number of flowers were studied in an arbitrarily chosen population. A relatively high light requirement and low competitive ability to gain light are considered factors likely for the microdistribution pattern. Drosophyllum lusitanicum cannot compete for light in habitats with intense competition. Seeds from D. lusitanicum have reduced probability of germination when adult plants are already growing in the area. It is hypothesized that seed germination shows a similar pattern to flowering, viz over a considerable time rather than in a sudden flush. This strategy may be a key factor for the species' survival, representing attempts to take advantage of available resources, preventing intraspecific competition and, finally, preventing sudden total disappearance of a population, resulting from any catastrophic events due to natural causes or to human activity. As a result of this study, some conservation measures are suggested. (C) The Linnean Society of London.
The following values have no corresponding Zotero field: pub-location: 24-28 OVAL RD, LONDON NW1 7DX, ENGLAND publisher: ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD
Keywords: competition; competitive ability; Droseraceae; intraspecific competition; microdistribution pattern; Portugal; seed bank

Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B.; Gómez-Gutiérrez, J. M.; Moreno-Marcos, G. (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling

Mediterranean pasture dynamics: the role of germination - Espigares, T.; Peco, B. (Journal of Vegetation Science, 1993)
pastures were arranged along a gradient of sensitivity to temperature on the arrival of the first persistent rain. This sensitivity was manifested in both the total germination success of the species and the germination time profile. The different germination patterns of the species can provide competitive advantages depending on the autumn weather conditions.
Keywords: Autumn rain; Gradient; Phytotron; seed bank; Temperature; Weather fluctuation